A brave face : two cultures, two families, and the Iraqi girl who bound them together - Marlowe, Barbara; Marlowe, Teeba Furat; Keirn, Jennifer (W Publishing Group, an imprint of Thomas Nelson, 2019)
"The inspirational story of a woman who moved mountains to provide medical care for an Iraqi girl badly burned during a roadside attack, Barbara Marlowe's determination to fight for her future daughter highlights the way love can reach across both cultures and continents. Barbara Marlowe was in her fifties when she saw the photo that changed her life. It was a photo of four-year-old Teeba Furat Fadhil, whose face, head, and hands had been severely burned during a roadside bombing in the Diyala Province of Iraq when she was just nineteen months old. It was Teeba's eyes that captivated Barbara. They were wide, dark, and soulful. They seemed to cry out with a message across continents: Help me. The story of Barbara responding to that call is as inspiring as it is improbable. With a powerful faith and determination, Barbara overcame obstacle after obstacle to bring Teeba to the United States for medical treatments--and to ultimately offer a home. A Brave Face includes material written by Teeba and her Iraqi mother, Dunia, at key moments in their stories. The book also explores the connection forged between Barbara and Dunia over the past decade--a connection that has survived the strife of war and the horrors of Al-Qaeda and ISIS."--